The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5539/gjhs.v12n9p38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rational-Emotive Behavior Intervention on Managing Burnout Symptoms among Postgraduate Students in Public Universities

Abstract: Burnout symptom is an emotional and psychological imbalance commonly experienced by students of tertiary institutions. This unhealthy state of existence is capable of undermining the quality of health and academic performances resulting in exhaustion and disengagement. The current study therefore aimed to investigate the effect of rational-emotive behavior intervention -REBI on managing burnout symptoms among postgraduate students in public universities. This research was based on experimental design involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…Ogbuanya et al (2019) determined that the Rational-Emotional Behavior Therapy Program had a significant effect on reducing the burnout of students in the experimental group. Similar findings were obtained in another study by Igbokwe, Obande-Ogbuinya, Nwala, Ezugwu, and Ugwu (2020) which evaluated the effect of the Rational-Emotional Behavior Therapy Program on the reducing burnout symptoms, conducted with graduate students studying at state universities in Nigeria. In addition, a study evaluating the effect of burnout status and their attendance on the first-and second-year students at Erciyes University Faculty of Medicine determined that stress management education was effective in reducing burnout, especially the emotional exhaustion sub-dimension of medical students (Naçar, Baykan and Çetinkaya, 2012).…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Ogbuanya et al (2019) determined that the Rational-Emotional Behavior Therapy Program had a significant effect on reducing the burnout of students in the experimental group. Similar findings were obtained in another study by Igbokwe, Obande-Ogbuinya, Nwala, Ezugwu, and Ugwu (2020) which evaluated the effect of the Rational-Emotional Behavior Therapy Program on the reducing burnout symptoms, conducted with graduate students studying at state universities in Nigeria. In addition, a study evaluating the effect of burnout status and their attendance on the first-and second-year students at Erciyes University Faculty of Medicine determined that stress management education was effective in reducing burnout, especially the emotional exhaustion sub-dimension of medical students (Naçar, Baykan and Çetinkaya, 2012).…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…They determined that 88% of 23 studies meeting the criteria of the research were effective in reducing burnout. However, it is striking that there are few intervention studies aimed at reducing the burnout of university students (Igbokwe, Obande-Ogbuinya, Nwala, Ezugwu and Ugwu, 2020;Naçar, Baykan and Çetinkaya, 2012;Ogbuanya et al, 2019;Yedigöz Sönmez and Çapri, 2013). These results show the necessity and importance of intervention programs especially for reducing student burnout.…”
Section: Psikoeğitim Programının üNiversite öğRencilerinin Tükenmişlimentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of REBT's effectiveness in assisting students in managing burnout, our present finding supports several studies which found similar results in student population. [3][4][5]11,12,14,23] Heber et al [26] show that internet-based intervention effectively reduced symptoms of stress. The finding of Harrer et al [27] supports online intervention delivery for reducing patient symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigerian studies of the university student population, internal consistency reliability tests show that Cronbach a score for the OLBI-S ranges from 0.77 to 0.90. [3][4][5]11,12,14,23] This online intervention was guided with an adapted electronic version of the manual of rational emotive behavioral therapy for the management of burnout [2] and was delivered using the telegram app. This online REBT intervention comprised cognitive restructuring strategies and re-education to alter students' burnout beliefs.…”
Section: Methodsmentioning
confidence: 99%